Some would say the equation is already in vertex form. For others, you need to subtract 2

y-2 = 1/3(x-1)^2

_____

Where the vertex is (h, k), vertex form shows these values explicitly

y-k = a(x-h)^2

or

y = a(x-h)^2 + k

The first of these forms is the one I learned. It is readily recognized as a translation of

y = ax^2

to a new vertex position.

y-2 = 1/3(x-1)^2

_____

Where the vertex is (h, k), vertex form shows these values explicitly

y-k = a(x-h)^2

or

y = a(x-h)^2 + k

The first of these forms is the one I learned. It is readily recognized as a translation of

y = ax^2

to a new vertex position.